Suplemen Jus Daun Afrika (Vernonia amygdalina) dalam Air Minum terhadap Komposisi Kimia dan Kadar Malondialdehid Telur Puyuh (Coturnix coturnix japonica): African Leaf (Vernonia amygdalina) Juice Supplement in Drinking Water on the Chemical Properties of Quail Egg (Coturnix coturnix japonica) - Innaka Hasbullah; Z Wulandari; D M Suci (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
This study aimed to determine the effectiveness of African leaf juice supplements on the chemical properties of quail eggs. This research used 120 quails aged 8 weeks, which divided into 3 treatments and 5 replications. The experimental design used a completely randomized and the treatments were P0 : without the supplementation of African leaf juice as controls, P1: addition of 3 ml head-1 day-1 African leaf juice, and P2: addition of 6 ml head-1 day-1 African leaf juice (P2). The variables observed were moisture, ash, crude protein, ether extract, carbohydrate, malondialdehyde content (MDA), pH and water activity (Aw) in yolk and albumen. The results showed that moisture, ash, crude protein, ether extract, and carbohydrate content in egg yolks had no different effect compared to controls. Malondialdehid (MDA) content in the treatment of 3 ml head-1 day-1 and 6 ml head-1 day-1 of African leaf juice supplementation decreased 39.68% and 36.19% compared to control. Aw level in yolk and albumen significantly (p<0.05) decreased in 6 ml of African leaf juice supplementation, but no effect on the pH eggyolk and albumen. It was concluded that addition of 3 ml and 6 ml of African leaf juice head-1 day-1 could reduce the MDA content of egg yolk.